Transivitas dan Konteks Situasi dalam Teks Pidato Nadiem Makarim pada Hari Guru Sedunia 2021: Kajian Linguistik Sistemik Fungsional - Warits Kramadanu; Gusnawaty Gusnawaty; Tadjuddin Maknun; Muhammad Hasyim (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2022)
Abstract This study aims to describe transivity and its relationship to the context of the situation in Nadiem Makarim's speech on World Teachers' Day 2021 by using functional systemic linguistic theory as an analytical tool. This research is descriptive with a qualitative approach. The data source for this research is Nadiem Makarim's speech on world teacher's day 2021 which is accessed through the official website of the Ministry of Education and Culture. The method used is the listening method with a note-taking technique. Listening is in the form of reading the entire speech, then recording it and dividing it into clauses. The results showed that from the 25 clauses, there were two participants, namely human participants and non-human participants. Human participants became the participants with the most occurrences. There were five types of processes which consisted of material, mental, relational, existential and verbal processes. The type of material process is the process that occurs most frequently. There were five circumstantials which consisted of circumstantial causes, methods, locations, ranges and views. The circumstantial most commonly found is the cause circumstantial. Based on the results of the transivity research in relation to the context of the situation, it can be seen that Nadiem Makarim wants to emphasize that work ethic, competence and real action are important things in advancing education in Indonesia, especially during this pandemic.